Jejunal mesenteric lymphangioma treated by pancreaticoduodenectomy: A case report. (2020) - Kitamura, Hirotaka; Yamamoto, Daisuke; Kadoya, Shinichi; Bando, Hiroyuki; Okayama, Yurie; Minato, Hiroshi
Highlights: Small bowel mesenteric lymphangiomas in adults are rare. A huge lymphangioma infiltrated the pancreas and duodenum. A pancreaticoduodenectomy was required to remove it completely. Abstract: Introduction: A lymphangioma is a benign congenital malformation of the lymphatic system that generally appears in the head, neck, and axillary regions. Small bowel mesenteric lymphangiomas have been described in less than 1% of lymphangiomas. Presentation of case: We report the case of a 20-year-old woman who presented with abdominal pain. Computed tomography revealed a large (22 cm in diameter) multi-cystic lesion inferior to the processus uncinatus of the pancreas. As the presumptive diagnosis was a lymphangioma of the jejunal mesentery, we decided to perform a laparotomy. Intraoperatively, the peritoneal cavity was found to be fully occupied by a multi-cystic lesion that arose from the root of the jejunal mesentery and the processus uncinatus of the pancreas. It was adherent to the duodenum and inseparable from the duodenum and the processus uncinatus. A subtotal stomach-preserving pancreaticoduodenectomy was performed. The tumor was diagnosed as a lymphangioma of the jejunal mesentery after histopathological analysis. Discussion: Although lymphangioma is benign, complete resection, including resection of the involved organs, is necessary. Incomplete resection has a 10% postoperative recurrence rate and may also be associated with complications. To the best of our knowledge, this is the first reported case of a mesenteric lymphangioma treated by pancreaticoduodenectomy. Conclusion: Although the lymphangioma was pathologically benign, a pancreaticoduodenectomy was required to remove it completely. When a tumor's location and size cause impingement on surrounding structures, surgeons should consider performing a pancreaticoduodenectomy to treat similar cases.